2020
DOI: 10.1002/rcm.8570
|View full text |Cite
|
Sign up to set email alerts
|

Native ion mobility mass spectrometry reveals that small organic acid fragments impart gas‐phase stability to carbonic anhydrase II

Abstract: Ion Mobility Mass Spectrometry (IMMS) reveals that small organic acid fragments impart gasphase stability to carbonic anhydrase II', Rapid communications in mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Following the commercialization of quadrupole/TWIMS/time-of-flight mass spectrometers 4 , modern technological developments have further extended the range of CIU examples. Current applications of CIU encompass probing protein-protein complexes 12,13 , protein-ligand interactions 9,[14][15][16][17][18] , and binding of lipids to membrane proteins 19,20 . CIU also plays a key role to investigate therapeutically-relevant proteins, allowing more conformational insights into monoclonal antibodies (mAbs) [21][22][23][24] , biosimilars 25 and antibody-drugconjugates 26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the commercialization of quadrupole/TWIMS/time-of-flight mass spectrometers 4 , modern technological developments have further extended the range of CIU examples. Current applications of CIU encompass probing protein-protein complexes 12,13 , protein-ligand interactions 9,[14][15][16][17][18] , and binding of lipids to membrane proteins 19,20 . CIU also plays a key role to investigate therapeutically-relevant proteins, allowing more conformational insights into monoclonal antibodies (mAbs) [21][22][23][24] , biosimilars 25 and antibody-drugconjugates 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Following the commercialization of quadrupole/TWIMS/time-of-flight mass spectrometers, modern technological developments have further extended the range of CIU examples. Current applications of CIU encompass probing protein–protein complexes, , protein–ligand interactions, , and binding of lipids to membrane proteins. , CIU also plays a key role to investigate therapeutically relevant proteins, allowing more conformational insights into monoclonal antibodies (mAbs), biosimilars, and antibody–drug conjugates. , In particular, Tian et al demonstrated that subtle differences between intact mAbs subclasses, with different numbers and patterns of disulfide bridges, could be distinguished based on their gas-phase unfolding. Recently, Botzanowski et al expanded this strategy to the middle-level classification of mAbs subclasses, which provides a more clear-cut categorization than the intact level …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Until now, native electrospray ionization mass spectrometry (native ESI-MS) has emerged as a powerful analytical approach to probe the protein-ligand (P-L) interactions. 3,4 This method employs the soft ionization technique ESI to transfer the intact P-L complexes from the liquid phase to the gas phase to conserve the weak non-covalent interaction. 5 P-L complexes with millimolar dissociation constants (K d ) can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Whilst conventionally underutilised, the speed and sensitivity inherent to native mass spectrometry (MS) has seen it emerge as a powerful fragment screening technique, which is capable of detecting weak interactions between unlabelled and untethered small molecular fragments and target proteins in the gas phase. [8][9][10][11] MS ligand binding experiments typically look to detect a molecular ion correlating to the apo protein in its native state (M) with the emergence of a new ion corresponding to the deconvoluted molecular mass of the proteinligand complex (M•L) indicating ligand binding. Comparison of the relative intensities of these ion peaks provides a rough indication of binding strength.…”
Section: Introductionmentioning
confidence: 99%